101 Embouchure dystonia complicating a case of focal cerebral vasculitis. (23rd August 2021) - Fontes-Villalba, Ariadna; Fernando, Suran; Parratt, John
Abstract : Background: Primary central nervous system vasculitis (PCNSV) is a rare disorder that normally develops with bilateral brain lesions. We report a case of pathologically confirmed hemispheric PCNSV with associated brain atrophy and symptoms of focal dystonia. Method: Case report. Result: A 45-year-old female presented with fluctuating apraxia, dystonia, cognitive dysfunction and numbness of the face. She had embouchure dystonia. She was taking lamotrigine for a longstanding history of well controlled partial seizures. A cerebral MRI revealed multiple left hemispheric cortical and subcortical white matter lesions. Many of the lesions enhanced. The lesions came and went over a period of three years but cortical atrophy of the fronto-parietal gyri developed. The CSF demonstrated matched oligoclonal bands. The autoimmune serology was negative. A cerebral PET demonstrated hypo-metabolism in the affected areas.A cortical lesion that was enhancing was biopsied and the histology showed several small foci of punctuate necrosis (infarcts) with lymphohistiocytic infiltration of blood vessels consistent with small vessel vasculitis. The patient was treated with prednisone and mycophenolate and improved clinically, albeit her clarinet playing did not return to pre-morbid levels. The MRI lesions resolved and did not recur. Conclusion: Focal vasculitis is rare but may result in neuronal loss and specific cortical damage and atrophy, in this case leading to embouchure dystonia. References: Salvarani C, Brown RD Jr, Hunder GG. Adult primary central nervous system vasculitis. Lancet 2012 Aug 25;380(9843):767–77. Ho MG, Chai W, Vinters HV, Hathout G, Mishra S, Yim C, Valdes-Sueiras M, Nishimura R. Unilateral hemispheric primary angiitis of the central nervous system. J Neurol 2011 Sep;258(9):1714–6. Unihemispheric central nervous syste.